Mortality attributable to poor dietary patterns in Canada: Evidence from the nationally-representative nutrition survey linked with health administrative data. (2018) - Jessri, Mahsa; Hennessy, Deirdre; Sanmartin, Claudia; Eddeen, Anan Bader; Manuel, Doug
No abstract available